2005
DOI: 10.1103/physrevlett.94.196803
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Skyrmion Crystallization from NMR Relaxation Experiments

Abstract: A resistively detected NMR technique was used to probe the two-dimensional electron gas in a GaAs/AlGaAs quantum well. The spin-lattice relaxation rate (1/T1) was extracted at near complete filling of the first Landau level by electrons. The nuclear spin of 75 As is found to relax much more efficiently with T → 0 and when a well developed quantum Hall state with Rxx ≃ 0 occurs. The data show a remarkable correlation between the nuclear spin relaxation and localization. This suggests that the magnetic ground s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 28 publications
6
51
0
Order By: Relevance
“…The matrix Γ N M R (ξ) takes into account the net rate of transition between consecutive nuclear spin levels depending on the energy of the RF frequency photons ( ω) and is given by (details given in Appendix D): 26) with τ N M R being of the order of 100µs [4,5]. It can be shown that when η → 0, in the absence of RF field perturbation, (16) becomes identical to (8).…”
Section: B Resistively Detected Nuclear Magnetic Resonance (Rdnmr)mentioning
confidence: 99%
See 2 more Smart Citations
“…The matrix Γ N M R (ξ) takes into account the net rate of transition between consecutive nuclear spin levels depending on the energy of the RF frequency photons ( ω) and is given by (details given in Appendix D): 26) with τ N M R being of the order of 100µs [4,5]. It can be shown that when η → 0, in the absence of RF field perturbation, (16) becomes identical to (8).…”
Section: B Resistively Detected Nuclear Magnetic Resonance (Rdnmr)mentioning
confidence: 99%
“…Using this approach, we show that the hysteresis noted in both the conductance and the RDNMR traces [3,11,18,19,[21][22][23][24][25][26] results from a lack of steady state between electronic transport and nuclear polarization evolution and can be explained by taking into account the finite rate of electron-nuclear spin flip-flops in a source limited channel in addition to a finite nuclear spin-lattice relaxation time. The self-consistent simulation framework between the nuclear spin dynamics and the edge state electronic transport developed here offers crucial insights into the dynamic nuclear polarization effects on electronic transport and in turn the electron-spin polarization effects on the nuclear spin dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar behavior was observed by Tracy et al [194]. In contrast, Gervais et al found in the same temperature range an increased relaxation when cooling the system [195]. For small deviations from = 1, Fig.…”
Section: Resultsmentioning
confidence: 49%
“…This interaction opened up opportunities to study quantum Hall states (QHSs) via nuclear magnetic resonance (NMR) spectra. For instance, the NMR combined with the resistance detection technique was used to investigate the dynamic nuclear spin polarization [1][2][3][4][5][6] and Skyrmion physics [7][8][9] in the quantum Hall effect (QHE) regime. NMR also allowed sensitive probing of the electron spin polarization of the QHE phases using the Knight shift of the resonance lines [10][11][12][13] and more recently probing of the local electron density in quantum solids.…”
mentioning
confidence: 99%